MANFAAT SERTIFIKASI RAINFOREST ALLIANCE (RA) DALAM MENGEMBANGKAN USAHATANI KOPI YANG BERKELANJUTAN DI KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Nita Oktami; Fembriarti Erry Prasmatiwi; Novi Rosanti (Lampung University, 2014)
This research purposes to study the benefits of Rainforest Alliance (RA) certificate in developing the sustainability of coffee farming from the aspects of economy, environmental, social and to analyze the factors that affect farmers to adopt sustainable coffee farming. The study was conducted in Pulau Panggung Sub Districts of Tanggamus Regency. This study compares the coffee farm management of certified farmers and noncertified farmers. There are 39 farmers chosen from each of coffee farming types. The benefits of RA certified for sustainability of coffee farming based on the increasing productivity, cost efficiency, and income of farmers were analyzed by t-test. The different test of Mann-Whitney U test is used to analyze the assessment of coffee farming management. The logit analysis method is used to analyze the factors that influence the farmers’ decisions. The research results showed that from the economy aspect, RA certification had benefits in terms of farmers management practices to increase the quality and cost control of coffee, but it had not yet benefit to increase the income, productivity and cost efficiency of coffee farming. Similarly, RA certification had benefits in terms of environmental and social, in which the results of the assessment of sustainable coffee farm management by certified farmers were significantly higher. Farmers' income and participation in RA certification program had positive effect on farmers to implement sustainable coffee farming. Key words : certification, coffee farming, sustainability